Interpretation of Autosomal Recessive Kidney Diseases With “Presumed Homozygous” Pathogenic Variants Should Consider Technical Pitfalls - Deng, Haiyue; Zhang, Yanqin; Yao, Yong; Xiao, Huijie; Su, Baige; Xu, Ke; Guan, Na; Ding, Jie; Wang, Fang (Frontiers in Pediatrics, 2020)
Background A false interpretation of homozygosity for pathogenic variants causing autosomal recessive disorders can lead to improper genetic counselling. The aim of this study was to demonstrate the underlying etiologies of presumed homozygous disease-causing variants harboured in 6 unrelated children with five different genetic renal diseases when the same variant was identified in a heterozygous state in only one of the two parents from each family using direct sequencing. Methods Peripheral blood genomic DNA samples were extracted. Six short tandem repeats were used to verify the biological relationships between the probands and their parents. Quantitative PCR was performed to detect mutant exons with deletions. Single nucleotide polymorphism analysis and genotyping with polymorphic microsatellite markers were performed to identify uniparental disomy (UPD). Results Each proband and his/her parents had biological relationships. Patients 2, 4 and 6 were characterized by large deletions encompassing a missense/small deletion in DGKE, NPHP1, and NPHS1, respectively. Patients 1 and 5 were caused by segmental UPD in NPHS2 and SMARCAL1, respectively. In patient 6, maternal UPD, mosaicism in paternal sperm or de novo variant in NPHP1 could not be ruled out. Conclusions When a variant analysis report shows that a patient of non-consanguineous parents has a pathogenic presumed homozygous variant, we should remember the need to assess real homozygosity for the variant, and a segregation analysis of the variants within the parental DNAs and comprehensive molecular tests to evaluate the potential molecular etiologies, such as a point variant and an overlapping exon deletion, UPD, germline mosaicism and de novo variant, are crucial.